PENERAPAN PASAL 264 AYAT (1) KUHP DALAM PEMIDANAAN PEMALSUAN AKTA NIKAH STUDI PUTUSAN (NOMOR 1471/Pid.B/2019/PN Jkt. Utr.) - Velia Audia Septian; R. Rahaditya (Jurnal Hukum Adigama, 2021)
Forgery of letters can have a manipulative effect on the originality of the contents of a letter. The provisions for forgery of letters containing in the Criminal Code Articles 263 to Article 276. This research aims to know how the application of Article 264 paragraph (1) of the Criminal Code in criminalizing marriage certificate falsification in (Study of Decision Number 1471/Pid.B/2019/PN. Jkt. Utr.). The research method used in this study is a normative research method, and the research specification is descriptive. The legal materials in this study are primary, secondary, and tertiary with a law and case approach. The results of this study illustrate that the criminal act of forgery committed by the Decision Number 1471/Pid.B/2019/PN. Jkt. Utr. has been proven that Wawan Setiawan as Defendant was right in committing the crime of falsifying the marriage certificate and marriage book. Therefore, the Defendant’s actions caused losses from various parties as wel as loss of confidence in the authentic deed. The perpetrators of the crime of falsifying authentic deeds in this case should be get punishment in accordance under legal provisions, that is violation of Article 264 paragraph (1) of the criminal code. Whereas, the criminal act of forging letters, the elements of which are in Article 263 of the Criminal Code. Article 264 paragraph (1) regulated of the criminal code and the punishment is even more severe if the forged is an authentic deed. Thus, in determining a crime, it is necessary to pay attention to the elements of the article given so that the sentence imposed is appropriate and fair